Pre- and Apnoeic high flow oxygenation for RApid sequence intubation in The Emergency department (Pre-AeRATE): study protocol for a multicentre, randomised controlled trial - Chua, Mui Teng (BMC, 2019)
10.1186/s13063-019-3305-8